Targeting the microbiota in the management of gastrointestinal and liver disease - Quigley, Eamonn MM (2017)
Thanks to rapid advances in technology the details of the human microbiome and its functions in health and disease are being progressively revealed. Though many reports have linked various disease states with an altered microbiome and while some associations between the microbiome and disease states are well established, many of these studies are largely descriptive and the changes reported in the microbiome have yet to be shown to be causative. A number of strategies are available to modify the microbiota; some such as the use of antibiotics for specific indications, are well established, others such as the use of probiotics and prebiotics in a variety of disease states are supported by more limited data. Fecal transplantation has emerged as an exciting, albeit rather drastic, intervention for intestinal and, perhaps, other disorders. Other approaches, such as the isolation, purification and formulation of small molecules with specific biological actions, derived from the microbiota look very promising